2009
DOI: 10.1007/s11237-009-9103-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cerium dioxide on the properties of monolithic CuO-ZnO-CeO2/Al2O3/cordierite catalysts in methanol decomposition

Abstract: Cerium dioxide as a component of CuO-ZnO-CeO 2 /Al 2 O 3 /cordierite catalysts stabilizes their action in the decomposition of methanol by preventing carbon deposition on the surface and facilitating hydrogen formation with selectivity and yield in the range 85-96%. The optimal indices for this reaction are obtained for a CeO 2 -CuO/Al 2 O 3 /cordierite sample prepared using an ammonium precursor for cerium, (NH 4 ) 2 Ce (NO 3 ) 6 . This catalyst displays enhanced reductive capacity relative to the analogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Further, the interaction between rare earth metals and transition metals can also be employed to improve catalyst capacity such as oxygen storage capacity and thermal stability. It was found that adding rare earth metals can prevent the growing of CuO or Cu 2 O grains under sintering conditions, , affording more even crystal size and pore size distribution. Meanwhile, because Cu and Ce ions possess distinctively different valences and radii, it is comparatively easier to form lattice defects and oxygen vacancies on the surface of the modified carbon material, which should improve the purification performance of adsorbent accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the interaction between rare earth metals and transition metals can also be employed to improve catalyst capacity such as oxygen storage capacity and thermal stability. It was found that adding rare earth metals can prevent the growing of CuO or Cu 2 O grains under sintering conditions, , affording more even crystal size and pore size distribution. Meanwhile, because Cu and Ce ions possess distinctively different valences and radii, it is comparatively easier to form lattice defects and oxygen vacancies on the surface of the modified carbon material, which should improve the purification performance of adsorbent accordingly.…”
Section: Introductionmentioning
confidence: 99%